Oprah Winfrey Talk Show: An Analysis of the Relationship between Positive Politeness Strategies and Speaker’s Ethnic Background (KEMANUSIAAN The Asian Journal of Humanities, 2019)
This research paper analysed the positive politeness strategies used by Oprah Winfrey and her guests in the Oprah Winfrey Talk Show. By analysing four full interviews for each group (African-Americans and Caucasians), the study also aimed to investigate the effect of the speaker’s ethnic background on the use of positive politeness strategies in Oprah Winfrey Talk Show. Based on Brown and Levinson’s (1987) politeness framework, the study revealed that both Oprah and her guests employed positive politeness strategies when addressing each other to avoid face threatening or face damage. The data also revealed that Oprah and her Caucasian guests used more positive politeness strategies than with the African-Americans. In addition, it was found that the most frequently used strategies in Oprah’s talk with both groups were “Seek agreement”, “Exaggerate (interest, approval, sympathy with H)”, “Give (or ask for) reasons”, “Presuppose/raise/assert common ground” and “Assert or presuppose S’s knowledge of and concern for H’s wants”, respectively. However, the study showed that there was a difference in the use of positive politeness strategies due to the addressee’s ethnic group background (African-American and Caucasian). However it was not dominant. Based on the findings, this article concludes with some implications for foreign/second language speakers.